Digitalization Trends in Education and Blended Learning - V. Danilov, Andrew; D. Nekrasova, Inna; Anyameluhor, Nnamdi (International Journal of Criminology and Sociology, 2022)
The article under review actualizes the problem of using digital computer technologies in the process of blended learning. The notion of «blended learning» is determined and specified according to various sources. Various models and ways of organizing this kind of work as an alternative to the standard form of learning are presented. The article presents a positive experience of using blended learning technology. Much attention is paid to visualization as one of the teaching tools to create educational materials for blended learning. The synthesis of verbal materials (especially spoken) and visual elements (pictures, graphic notes, animations, films, plots, and diagrams, etc.) within the limits of one text is an instrument to optimize the process of semantic perception and understanding text information. All the benefits of this modern technology allow students to establish a holistic adoption of this model and a positive direction for the development of blended learning as an innovative teaching technology